Peran Filsafat Pendidikan Islam dalam Membangun Pendidikan Karakter Siswa Kelas IV SD Negeri Ajibarang Wetan - Desianto; Khoirul Azis, Donny (Jurnal Nusantara Raya, 2025)
This study aims to describe the role of Islamic educational philosophy in building the character education of fourth-grade students at SD Negeri Ajibarang Wetan. The background of this research arises from the growing need to strengthen character education in elementary schools amid increasingly complex moral and social challenges. Islamic educational philosophy is considered relevant because it emphasizes a balance between intellectual, emotional, and spiritual development rooted in the values of tawhid (divine unity), adab (ethics), and human responsibility as khalifah (steward) on earth. This research employed a qualitative approach with a case study design. Data were collected through classroom observations, interviews with teachers, the principal, and students, as well as document analysis. The findings reveal that Islamic educational values have been effectively integrated into learning activities, school culture, and religious practices. Teachers implement the principles of ta’dib (moral education), uswah hasanah (exemplary conduct), and muhasabah (self-reflection) to shape students’ character. These practices have resulted in positive behavioral changes such as honesty, responsibility, discipline, and social care. However, the study also found that teachers’ understanding of the philosophical foundations of Islamic education varies, indicating the need for further professional development to strengthen conceptual and reflective competence. The implications of this study highlight the importance of systematically integrating Islamic educational philosophy within the Merdeka Curriculum to develop students who are morally upright, religiously aware, and intellectually balanced.